2019
DOI: 10.1007/s12374-019-0056-8
|View full text |Cite
|
Sign up to set email alerts
|

Killing two birds with one stone: How do Plant Viruses Break Down Plant Defenses and Manipulate Cellular Processes to Replicate Themselves?

Abstract: As simple organisms with a parasite nature, viruses have become masters in manipulating and subvert cellular components, including host proteins and organelles, to improve viral replication. Therefore, the understanding of viral strategies to manipulate cell function disrupting plant defenses and enhancing viral infection cycles is fundamental to the production of virus-resistant plant lines. After invading susceptible plants, viruses create conditions that favor local and systemic infections by suppressing mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 81 publications
0
13
0
Order By: Relevance
“…2b). Several research works have shown that viruses can interact with chloroplast proteins and induce the formation of membrane vesicles during viral replication, which impairs chloroplast functions in plants (Liu et al 2014; Li et al 2016a; Zhao et al 2016; Souza and Carvalho 2019). For example, high levels of Potato virus X (PVX, Potexvirus )-Coat Protein (CP) caused structural alteration of the chloroplast membranes, thylakoid grana and invagination of the cytoplasm within these organelles; it was also found to interact with the plastocyanin (Zhao et al 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2b). Several research works have shown that viruses can interact with chloroplast proteins and induce the formation of membrane vesicles during viral replication, which impairs chloroplast functions in plants (Liu et al 2014; Li et al 2016a; Zhao et al 2016; Souza and Carvalho 2019). For example, high levels of Potato virus X (PVX, Potexvirus )-Coat Protein (CP) caused structural alteration of the chloroplast membranes, thylakoid grana and invagination of the cytoplasm within these organelles; it was also found to interact with the plastocyanin (Zhao et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…To enable their multiplication, plant viruses have the ability to rearrange host metabolism and cellular machinery (Souza and Carvalho 2019). A wide range of physiological and biochemical disorders are triggered from cell infection, including relocation of photoassimilates, redox imbalance and premature senescence, with significant economic losses (Rodríguez et al 2010, 2012; Souza and Carvalho 2019). Viral infections lead to a decline in CO 2 fixation, which could be directly related to a decrease in carbohydrate accumulation, reducing plant growth and development (Sade et al 2013; Nuwamanya et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…S protein is not called here as a principal actor without a motive. In some cases, during CoVs, the infection can lead to the formation of syncytia [ [206] , [207] , [208] ].…”
Section: Biological Roles Of the S Proteinmentioning
confidence: 99%
“…Syncytia are giant infected cells induced by some viruses, like coronaviruses. All pandemic coronaviruses, SARS-CoV-1, MERS-CoV and SARS-CoV-2 [ [206] , [207] , [208] ] have the ability to induce syncytia formation. Somehow, in coronavirus infection, the host cell showed the S protein on the membrane, which is a quite important function of S protein.…”
Section: Biological Roles Of the S Proteinmentioning
confidence: 99%
“…Although plant viruses contain relatively simple genomes, the molecular basis of the mechanisms by which they infect their hosts and the signaling components involved in host resistance are not well-defined [ 73 ], and CPsV is no exception. Furthermore, the mechanisms underlying molecular and biochemical changes during compatible and incompatible plant–virus interactions are only beginning to be deciphered, including changes in proteomic profiles induced by virus infections [ 74 ]. It is possible that signaling pathways may occur upon the infection of citrus by CPsV.…”
Section: Signaling Pathways In Citrus Psorosis Pathogenesismentioning
confidence: 99%